(untitled) (The Pretoria Student Law Review, 2021)
This article is underscored by the importance of expect witnesses on court cases but also the realisation that expert witnesses are often beyond the means of those who need them. An analogy is drawn between the pro bono work that legal practitioners must do and the idea that medical practitioners can serve as expert witnesses as part of their pro bono work. This article will critically evaluate whether medical practitioners should be required to give themselves a certain number of pro bono hours to serve as expert witnesses.